Training of pedagogical staff - strategic goal of innovative university. engineering competencies -traditions and innovations - Chuchalin A. I. Alexander Ivanovich; Minin M. G. Mikhail Grigoryevich; Safyannikov I. A.; Belomestnova E. N.; Vyuzhanina N. Y. (2008, 2008)
В фонде НТБ ТПУ отсутствует